The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/pas.0000000000000598
|View full text |Cite
|
Sign up to set email alerts
|

Barrett’s Esophagus

Abstract: This review provides a summary of our current understanding of, and the controversies regarding, the diagnosis, pathogenesis, histopathology, and molecular biology of Barrett's esophagus (BE) and associated neoplasia. Barrett's esophagus is defined as columnar metaplasia of the esophagus. There is worldwide controversy regarding the diagnostic criteria of BE, mainly with regard to the requirement to histologically identify goblet cells in biopsies. Patients with BE are at increased risk for adenocarcinoma whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(49 citation statements)
references
References 181 publications
(225 reference statements)
0
48
0
1
Order By: Relevance
“…Assuming adequate biopsies are taken, technical or processing artifact of the tissue can hinder accurate determine of dysplasia. 10 Histological interpretation of biopsies is more challenging when active inflammation and ulceration are present, which is not uncommon in patients with Barrett’s esophagus. Inflammation induces regenerative changes in the Barrett’s epithelium and these regenerative changes can mimic dysplasia.…”
Section: Limitations With Using Dysplasia To Stratify Cancer Risk Inmentioning
confidence: 99%
See 3 more Smart Citations
“…Assuming adequate biopsies are taken, technical or processing artifact of the tissue can hinder accurate determine of dysplasia. 10 Histological interpretation of biopsies is more challenging when active inflammation and ulceration are present, which is not uncommon in patients with Barrett’s esophagus. Inflammation induces regenerative changes in the Barrett’s epithelium and these regenerative changes can mimic dysplasia.…”
Section: Limitations With Using Dysplasia To Stratify Cancer Risk Inmentioning
confidence: 99%
“…This can lead to diagnostic uncertainty and may result in a biopsy specimen labeled “indefinite for dysplasia”, leading to the need for repeat endoscopy with biopsies. 10 This issue of inflammation mimicking dysplasia is the rationale underlying the recommendation in the American College of Gastroenterology (ACG) guidelines which advises against taking biopsies in areas of erosive esophagitis until after intensive anti-secretory therapy has healed any mucosal injury. 3 …”
Section: Limitations With Using Dysplasia To Stratify Cancer Risk Inmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many theories concerning the origin of a BE and no consensus has been reached, as was stated by the authors of a recent review [3]. They concluded that Barrett glands are more complex and possibly unique within the human gastrointestinal epithelium.…”
Section: Introductionmentioning
confidence: 99%